2015
DOI: 10.1371/journal.pntd.0003925
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Rhesus Macaques Self-Cure from a Schistosoma japonicum Infection by Disrupting Worm Esophageal Function: A New Route to an Effective Vaccine?

Abstract: BackgroundRhesus macaques are unusual among schistosome hosts, self-curing from an established infection and thereafter manifesting solid immunity against a challenge, an ideal model for vaccine development. Previously, the immunological basis of self-cure was confirmed; surviving worms had ceased feeding but how immunological pressure achieved this was unclear. The schistosome esophagus is not simply a conduit for blood but plays a central role in its processing. Secretions from the anterior and posterior eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 33 publications
8
61
0
Order By: Relevance
“…We observed significant increases in populations of LN‐ and LPL‐derived CD3 – CD20 + B cells stimulated with either SmEA and/or SmWA compared with the unstimulated negative control. This finding is supported by other studies that have described the roles of antibodies in the mechanism of schistosome resistance of rhesus macaques to infection . Interestingly, we observed a significant increase in the magnitude of the response of B cells stimulated with SmEA or SmWA+SmEA compared with B cells stimulated with SmWA only (from all tissues examined; PBMCs, LN, and gut LPLs), consistent with the hypothesis that antibody‐mediated schistosome killing in infected macaques maybe be associated with the onset of egg‐laying by the female worms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We observed significant increases in populations of LN‐ and LPL‐derived CD3 – CD20 + B cells stimulated with either SmEA and/or SmWA compared with the unstimulated negative control. This finding is supported by other studies that have described the roles of antibodies in the mechanism of schistosome resistance of rhesus macaques to infection . Interestingly, we observed a significant increase in the magnitude of the response of B cells stimulated with SmEA or SmWA+SmEA compared with B cells stimulated with SmWA only (from all tissues examined; PBMCs, LN, and gut LPLs), consistent with the hypothesis that antibody‐mediated schistosome killing in infected macaques maybe be associated with the onset of egg‐laying by the female worms.…”
Section: Discussionsupporting
confidence: 91%
“…The antibody‐mediated processes are believed to obstruct blood‐feeding mechanisms of the worms . Electron microscopic studies revealed antibody‐mediated damages to the esophagus architecture and function of the adult worms as shown with the disruption of the anterior vesicle secretory process . Immunoproteomics studies have identified schistosome gut digestive enzymes, tegument surface hydrolases, and antioxidant enzymes as targets of macaques’ antibodies …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, infections with the related Schistosoma spp. in species such as humans (Agnew et al, 1996;Cheever et al, 1977;Drake and Bundy, 2001), primates (Cheever et al, 1974;He et al, 1992;Li et al, 2015), water buffalo (Li, 2014), cattle and pigs (Vercruysse and Gabriel, 2005) generally decrease in intensity as the host ages. Meanwhile, the ability of poikilotherms to develop immune responses to blood flukes is demonstrated by the progressive development of humoral responses by Pacific Bluefin tuna (Thunnus maccoyii) to aporocotylid flukes (Cardicola spp.)…”
Section: Discussionmentioning
confidence: 99%